Review on Carbon Capture in ICE Driven Transport - Alexander García-Mariaca (MDPI AG, 2021)
The transport sector powered by internal combustion engines (ICE) requires novel approaches to achieve near-zero CO2 emissions. In this direction, using CO2 capture and storage (CCS) systems onboard could be a good option. However, CO2 capture in mobile sources is currently challenging due to the operational and space requirements to install a CCS system onboard. This paper presents a systematic review of the CO2 capture in ICE driven transport to know the methods, techniques, and results of the different studies published so far. Subsequently, a case study of a CCS system working in an ICE is presented, where the energy and space needs are evaluated. The review reveals that the most suitable technique for CO2 capture is temperature swing adsorption (TSA). Moreover, the sorbents with better properties for this task are PPN-6-CH2-DETA and MOF-74-Mg. Finally, it shows that it is necessary to supply the energy demand of the CCS system and the option is to take advantage of the waste heat in the flue gas. The case study shows that it is possible to have a carbon capture rate above 68% without affecting engine performance. It was also found that the total volume required by the CCS system and fuel tank is 3.75 times smaller than buses operating with hydrogen fuel cells. According to the review and the case study, it is possible to run a CCS system in the maritime sector and road freight transport.